Representation of Post-War Trauma in Soniah Kamal’s An Isolated Incident - Sumbal Aziz; Bilal Asmat Cheema; Sana Nawaz, (Dialogue Social Science Review (DSSR), 2025)
The paper highlights the intersection of violence, loss and displacement in Soniah Kamal’s An Isolated Incident. It also explores the role of fragmented memories in disorienting the nature of trauma where past memories affect the present. The research article aims to explore the psychological effects of war illustrating how survivors struggle to reconcile their painful histories with their present, often reliving traumatic moments voluntarily through flashbacks. This study will apply theory of Psychoanalysis to analyze how characters in an isolated incident are trapped in trauma resulting in repression and denial. Through thorough examination, study reflects the damaged psychological state of survivors. Flashbacks serve as a representation of how unresolved trauma invades daily life. Post war trauma challenges personal and collective identity and not only shatters the individuals’ sense of self but also complicates the relationship with their homeland, history and community. The findings aim to contribute the deeper understanding the flashbacks and memories which endure the effects of Post war trauma.